Effects Of Islamic Studies On Non Muslims: A Case Of Economic Undergraduates - Shafinah Begum, Abdul Rahim (2016)
The provision of Islamic studies at schools, both public and public, is obligatory for all Muslim students in Malaysia since independence. However, at institutions of higher learning certain Islamic related courses have been made compulsory for all, including the non- Muslims. A case of interest is the offering of an introductory course on Islamic Economics by the Faculty of Economics and Business, UNIMAS to its final year candidates. To date, at least 700 graduates with a Degree in Economics from the University are exposed to the basic concepts and fundamentals of economics from the perspective of Quran and Sunnah. The purpose of this study is to explore the understanding of Islam in general and its implications on economic matters amongst the non-Muslims students. Subsequently, the objective is to investigate whether and how these students benefited from the new knowledge which was imposed on them. Another goal is to compare the motivation, commitment and performance between the Muslims and non-Muslim students in general. Information gathered from surveys and personal interviews clearly indicate that the non-Muslim students are open to Islamic economic ideas provided it is backed by strong evidences. A majority of the students claims that the course is a platform to clear doubts and misperceptions about Islam. The most appealing topics within the syllabus that draws the highest attention include the concepts of haram and halal relating to sources of income, relevance of zakat towards poverty and Islamic banking and finance. Given the 6 year record, the non- Muslim students have performed relatively better due to factors such as personal concern for final grade and the lack of background advantage owned by the Muslim students. Findings demonstrate that the course ought to be considered as an elective for all business programs, allowing increased participation from students from the Accounting, Finance, Marketing and Management Degree programs. However, the content and delivery need to be revised and adjusted to the respective practices to enable students to maximize their learning experience.